Cytomorphological assessment of the nasal mucosa of the children's population of some industrial cities of Karaganda region - Nurlybayeva, K.A.; Aitkulov, A.M.; Mukasheva, M.A.; Starikova, A.E. (KSU publ., 2018)
The article presents the results of studying rhinocytogram of the child population of three industrial cities of Karaganda region (Temirtau, Balkhash, Abai cities). The methods of cytological analyses of mucous membrane of the nasal cavity (MMNC) were used. Cytochemical methods were used for early detection of functional changes in the non-specific mononuclear system of protection of an organism from environmental factors. In the cytomorphologycal study of MMNC’s cell, it was found a reduced quantity of normal epithelial cells of children which live in Temirtau city (10.8 times) and in Balkhash city (12.1 times).. Students of Abai city had the 13.3 times decrease of indicators in the cells of flat epithelium. The number of segmental and rod-core neutrophils with signs of damage exceeded the physiological norms in the children's population of Abai (4.8 times), Temirtau (6.3 times), and Balkhash (7.4 times). Thus, with the help of indicators of bacterial contamination of the mucous membranes of the nasal cavity, it is possible to identify people who are at risk for non-specific diseases and have suppressed function of immune system.
Қарағанды облысындағы кейбір өнеркəсіптік қалалардағы балалардың мұрнының шырышты қабығы күйін цитоморфологиялық бағалау
Цитоморфологическая оценка слизистой оболочки полости носа у детского населения некоторых промышленных городов Карагандинской области
Keywords: mucous membrane of the nasal cavity; children's population; nonspecific resistance of an organism; eosinophils; mast cells